Build the EU Pollinator Monitoring Scheme on robust evidence - André Krahner; Anke C. Dietzsch; Tobias Jütte; Felix Klaus; Oleg Lewkowski; Severin Polreich; Jens Pistorius (Journal of Pollination Ecology)
Recently, the Proposal for an EU Pollinator Monitoring Scheme (EUPoMS) has been revised, presenting options for a standardised monitoring of insect pollinators across the EU. While we appreciate the overall EUPoMS approach, we argue that the adequacy of core methods in the revised EUPoMS is not substantiated by robust evidence. We consider it essential that the authors will make an effort in the near future to catch up on explaining the exclusion of pan traps from the EUPoMS Core Scheme to the scientific community. This will ultimately secure scientific and public trust in the EUPoMS.